Recognition of bacterial plant pathogens: local, systemic and transgenerational immunity. Issue 4 (20th March 2013) - Henry, Elizabeth; Yadeta, Koste A.; Coaker, Gitta
Summary: Bacterial pathogens can cause multiple plant diseases and plants rely on their innate immune system to recognize and actively respond to these microbes. The plant innate immune system comprises extracellular pattern recognition receptors that recognize conserved microbial patterns and intracellular nucleotide binding leucine‐rich repeat (NLR) proteins that recognize specific bacterial effectors delivered into host cells. Plants lack the adaptive immune branch present in animals, but still afford flexibility to pathogen attack through systemic and transgenerational resistance. Here, we focus on current research in plant immune responses against bacterial pathogens. Recent studies shed light onto the activation and inactivation of pattern recognition receptors and systemic acquired resistance. New research has also uncovered additional layers of complexity surrounding NLR immune receptor activation, cooperation and sub‐cellular localizations. Taken together, these recent advances bring us closer to understanding the web of molecular interactions responsible for coordinating defense responses and ultimately resistance.